(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Widiastuti T, Astiani D, Roslinda E, Ekyastuti W, Ekamawanti HA. 2024. Mangrove land cover changes in North Singkawang, West Kalimantan, Indonesia analyzed using Landsat 8 images. Biodiversitas 25: 3160-3167. North Singkawang District, located within Singkawang City in West Kalimantan Province, is a coastal area with significant potential for mangrove forests. Recently, the district has experienced considerable land use changes, including the conversion of land for settlements, fish ponds, agricultural purposes, and coastal abrasion at various locations. To support the sustainability of mangrove forests, it is crucial to gather data on the area and distribution of these forests. This study aimed to investigate changes in the area and distribution of mangrove forests within this district. A survey method was employed for this investigation. Mangrove vegetation was assessed using visual interpretation of Landsat 8 OLI_TIRS images from 2016, 2019, and 2022. The Geographic Information System (GIS) application, specifically ArcGIS 10.8 software, was utilized to create maps and analyze land cover changes. The total area of mangrove forest was 514.95 hectares. Land cover in the North Singkawang mangrove forest area, in 2016, 2019, and 2022, consisted of mangrove forests, community crop areas, fish ponds, and open fields. Between 2016 and 2019, open fields (45.81 hectares) and community crop areas (9.84 hectares) were converted into mangrove forests through reforestation. During the same period, deforestation occurred as natural mangrove forests were converted into community crop areas (36.49 hectares), and open fields were transformed into community crop areas (0.03 hectares). From 2019 to 2022, community crop areas (6.93 hectares) were converted into mangrove forests, while deforestation resulted in the conversion of mangrove forests to open fields (15.37 hectares). From 2016 to 2022, mangrove forest cover increased by 10.72 hectares, community crop areas expanded by 19.74 hectares, the area of fish ponds remained unchanged, and open fields decreased by 30.46 hectares. The increase in mangrove forest cover was attributed to natural regrowth and reforestation activities, while the reduction in mangrove forests was primarily driven by anthropogenic activities, particularly the conversion of mangrove forests for crop production.